Hubungan dukungan keluarga dengan kecemasan dalam menghadapi menarche pada siswi kelas IV, V, & VI - Wati, Riska Rahma; Rahman, Aulia; Sulastri, Diah (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Adolescence begins at the age of 10-19 years, during which time they will be faced with sexual maturity called the puberty phase. Menarche is when menstruation comes for the first time in a woman who is about to enter adulthood. The impact of menarche on adolescent girls is the emergence of psychological changes in the form of emotions, namely feelings of anxiety. The anxiety experienced by adolescents such as being shocked or even traumatized, afraid, being rational, and easily offended. Psychologically, the role of parents, especially mothers, is very important for adolescent girls. Purpose: To determine the relationship between family support and anxiety in facing menarche. Methods: Quantitative research with analytical correlation design and cross-sectional approach. The population of this study were female students in grades IV, V, VI at UPT SDN 01 SRI MULYA in 2025 who had not yet reached menarche. A total of 49 samples were used in the study using total sampling technique. Data collection using questionnaires which were then analyzed univariate and bivariate. Results: Bivariate analysis using the chi-square test to determine the relationship between family support and anxiety obtained results showing a significant relationship between the two variables with a p value of 0.000 (p ≤ 0.05). Conclusion: There is a relationship between family support and anxiety in facing menarche in grades IV, V, & VI.   Keywords: Anxiety; Family Support; Menarche.   Pendahuluan: Masa remaja dimulai sejak usia 10-19 tahun, pada masa tersebut akan dihadapkan dengan kematangan seksual yang disebut dengan fase pubertas. Menarche adalah saat haid/menstruasi yang datang pertama kali pada seorang wanita yang akan menginjak dewasa. Dampak dari menarche pada remaja putri yaitu timbulnya perubahan psikologis berupa emosional yaitu perasaan cemas. Kecemasan yang dialami remaja seperti terkejut bahkan trauma, takut, bersikap rasional, serta mudah tersinggung. Secara psikologis, peran orang tua terutama ibu sangat penting bagi seorang remaja putri. Tujuan: Untuk mengetahui hubungan dukungan keluarga dengan kecemasan dalam menghadapi menarche. Metode: Penelitian kuantitatif dengan desain korelasi analitik dan pendekatan cross sectional. Populasi penelitian ini siswi kelas IV, V, VI di UPT SDN 01 SRI MULYA tahun 2025 yang belum menarche. Sebanyak 49 sampel dalam penelitian dengan teknik total sampling. Pengambilan data menggunakan kuesioner yang kemudian dianalisis secara univariat dan bivariat. Hasil: Analisis bivariat menggunakan uji chi-square dalam mengetahui hubungan dukungan keluarga dengan kecemasan memperoleh hasil adanya hubungan yang bermakna antara kedua variabel dengan nilai p sebesar 0.000 (p ≤ 0.05). Simpulan: Ada hubungan dukungan keluarga dengan kecemasan dalam menghadapi menarche siswi kelas IV, V, & VI.   Kata Kunci: Dukungan Keluarga; Kecemasan; Menarche.